2022
DOI: 10.1017/wsc.2022.19
|View full text |Cite
|
Sign up to set email alerts
|

Development of a temperature-based seed germination model for silverleaf nightshade (Solanum elaeagnifolium)

Abstract: Silverleaf nightshade (Solanum elaeagnifolium Cav.) has become a highly troublesome weed in irrigated summer crops in Israel. Since herbicide-based options to control this weed are limited, the best way to improve weed control is through a study of its biology, particularly its germination dynamics. The main objective of this study was thus to determine the impact of temperature on the seed germination dynamics of S. elaeagnifolium and to develop a temperature-based (thermal) prediction model for three S. elae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…The model's effectiveness in predicting cardinal temperatures and the development of phenological events in various plant species has indeed been demonstrated previously (Cochavi et al 2016(Cochavi et al , 2018Yin et al 1995). Kapiluto et al (2022), who performed a study similar to the current one, but for seeds, revealed cardinal temperatures of 10.8, 23.8, and 35.9 C for T b , T o , and T c , respectively. It may be seen that these values for S. elaeagnifolium seeds and rhizomes differed mainly for T o and T c , which were higher by 12 and 5 C, respectively, among the rhizome fragments.…”
Section: Modeling Sprouting Rate As a Function Of Temperaturesupporting
confidence: 80%
See 3 more Smart Citations
“…The model's effectiveness in predicting cardinal temperatures and the development of phenological events in various plant species has indeed been demonstrated previously (Cochavi et al 2016(Cochavi et al , 2018Yin et al 1995). Kapiluto et al (2022), who performed a study similar to the current one, but for seeds, revealed cardinal temperatures of 10.8, 23.8, and 35.9 C for T b , T o , and T c , respectively. It may be seen that these values for S. elaeagnifolium seeds and rhizomes differed mainly for T o and T c , which were higher by 12 and 5 C, respectively, among the rhizome fragments.…”
Section: Modeling Sprouting Rate As a Function Of Temperaturesupporting
confidence: 80%
“…at 33 C (Satorre et al 1996) and yellow nutsedge (Cyperus esculentus L.) at 28 C (Li et al 2000), indicating the preference for high temperatures for sprouting of such plants. Furthermore, our results indicate that the maximum sprouting of S. elaeagnifolium rhizomes was higher by 10 C than that for seed germination (Kapiluto et al 2022). In general, rhizomes contain larger carbohydrate reserves than seeds, which in turn enable them to survive and sprout in extreme environments (Anbari et al 2011;Chen et al 2015;Mangoale and Afolayan 2020;Yu et al 2001).…”
Section: Impact Of Constant Temperatures On Solanum Elaeagnifolium Sp...mentioning
confidence: 68%
See 2 more Smart Citations
“…portulacastrum emergence under Israeli climatic conditions, where T. portulacastrum infests crops that are cultivated in the summer, such as maize, tomato, watermelon, setaria, and groundnut. In a similar thermal time model study on the perennial weed Solanum elaeagnifolium in Israel, T base for germination was computed to be 10.8°C (Kapiluto et al, 2022). A seed germination thermal time model was also used by Ottavini et al (2019), who studied the effects of light, temperature, and soil depth on the germination and emergence of the invasive weed Conyza canadensis (L.) Cronq.…”
Section: Germination Testsmentioning
confidence: 99%